GmWRKY31 and GmHDL56 Enhances Resistance to Phytophthora sojae by Regulating Defense-Related Gene Expression in Soybean - Fan, Sujie; Dong, Lidong; Han, Dan; Zhang, Feng; Wu, Junjiang; Jiang, Liangyu; Cheng, Qun; Li, Rongpeng; Lu, Wencheng; Meng, Fanshan; Zhang, Shuzhen; Xu, Pengfei (Frontiers in Plant Science, 2017)
Phytophthora root and stem rot (PRR) of soybean [Glycine max (L.) Merr.] caused by the oomycete Phytophthora sojae, is a destructive disease worldwide. The molecular mechanism of the soybean response to P. sojae is largely unclear. We report a novel WRKY transcription factor (TF) in soybean, GmWRKY31, in the host response to P. sojae. Overexpression and RNA interference analysis demonstrated that GmWRKY31 enhanced resistance to P. sojae in transgenic soybean plants. GmWRKY31 was targeted to the nucleus, where it bound to the W-box and acted as an activator of gene transcription. Moreover, we determined that GmWRKY31 physically interacted with GmHDL56, which improved resistance to P. sojae in transgenic soybean roots. GmWRKY31 and GmHDL56 shared a common target GmNPR1 which was induced by P. sojae. Overexpression and RNA interference analysis demonstrated that GmNPR1 enhanced resistance to P. sojae in transgenic soybean plants. Several pathogenesis-related (PR) genes were constitutively activated, including GmPR1a, GmPR2, GmPR3, GmPR4, GmPR5a and GmPR10, in soybean plants overexpressing GmNPR1 transcripts. By contrast, the induction of PR genes was compromised in transgenic GmNPR1-RNAi lines. Taken together, these findings suggested that the interaction between GmWRKY31 and GmHDL56 enhances resistance to P. sojae by regulating defense-related gene expression in soybean.